Mission, (self)-perception and role in localized food systems of Italian biodistricts: insights from a Delphi survey - Sturla, Alberto; Viganò, Laura; Vassallo, Marco; Belliggiano, Angelo (Frontiers in Sustainable Food Systems, 2024)
In Italy, the spread of biodistricts (BDs) is already affecting almost 30% of the national territory. Specific, eminently local reasons, alongside more general motivations, like a favorable political context and the improvement of accessibility to health and local food by all citizens influence the birth of a BD. Their development has been so fast that, despite the mounting interest in them by national and regional legislation and by relevant scientific and grey literature, there are still debated issues concerning the criteria for BD definition and identification, the governance models to be adopted and their functions and range of action, especially regarding the development of markets and supply chains. With the aim of settling these controversial aspects, so to reach an agreement on them among experts and therefore outline characteristics and possible courses of action for BDs as policy actors consistent with their mission, a three rounds Delphi study has been carried out. Starting from a series of 12 open questions, in the last round the survey got to concern the definition of the BD, its resilience in the event of a crisis, and its approach to the market. In respondents’ opinion BDs specificity resides in functions rather than on structural and organizational characteristics (e.g.: concentration of organic farming, presence of structured supply chain) that nevertheless must be taken as objective for meaningful territorial actions, to reach by activating local social capital. In this view, the development of interaction between producers and consumers and the satisfaction of local demand must be central in BDs strategy, but doesn’t preclude penetration in national and foreign market, whenever functional to local supply chains enhancement. Recent crises have been the test bench of BDs governance, showing that resilience is strongly dependent from their organizational maturity.